Three-dimensional analysis and airflow simulation using computational fluid dynamics of the upper airways in Treacher-Collins syndrome - Nunes, Rodrigo Barboza (2021)
Introduction: Treacher-Collins syndrome is often associated with upper airway obstruction and respiratory impairment. Objective: The objective of the study is to evaluate the upper airways of patients with the syndrome in three dimensions and to analyze the respiratory dynamics through simulations with computational fluid dynamics. Methods: The sample consisted of 14 cone beam computed tomographies from the HRAC-USP file; 6 male and 8 female, aged 6-20 years. The tomographic data were exported in DICOM (Digital Imaging and Communications in Medicine) to the software MIMICS 21.0 (Materialisms Software Interactive Medical Image Control System) and realistic models of the upper airways were generated and analyzed. Then, the models were exported as stereolithography (STL) files to the ANSYS worbench and simulations were performed using the FLUENT solver. Results: The minimum sectional area of the oropharynx presents values between 10.72-201.44 mm2. The angles formed between the nasal cavity / nasopharynx and the oropharynx vary between 107.65 º-153.56º. The volume of the nasal cavity varies between 5360.68-13582.96 mm3, the volume of nasopharynx between 179.06-3845.89 mm3 and the volume of the oropharynx between 3338.18-20137.16 mm3. The distance between the angle of the jaw and the location of the minimum sectional area varies between +10.52 mm and -18.10 mm. The fluid dynamics simulation revealed areas of increased air velocity and dynamic pressure in the oropharynx, great differences between the flow of the nostrils in most fluid dynamics analyzes performed, an important area of constriction in the nasopharynx in one case and oral breathing tendency in another analysis. Conclusion: Data from volumetry and computational fluid dynamics suggest that in Treacher-Collins syndrome is common the reduction in volume and obstruction of the nasal cavity/nasopharynx, which can induce the patient to mouth breathing and contribute to the collapse of the airways and worsening of facial deformities.